Integrated miRNA profiling and bioinformatics analyses reveal potential causative miRNAs in gastric adenocarcinoma - Zhang, Xiaojing (Oncotarget, 2015)
Gastric cancer (GC) is one of the leading causes of cancer-related deaths throughout China and worldwide. The discovery of microRNAs (miRNAs) has provided a new opportunity for developing diagnostic biomarkers and effective therapeutic targets in GC. By performing microarray analyses of benign and malignant gastric epithelial cell lines (HFE145, NCI-N87, MKN28, RF1, KATO III and RF48), 16 significantly dysregulated miRNAs were found. 11 of these were validated by real-time qRT-PCR. Based on miRWalk online database scans, 703 potential mRNA targets of the 16 miRNAs were identified. Bioinformatic analyses suggested that these dysregulated miRNAs and their predicted targets were principally involved in tumor pathogenesis, MAPK signaling, and apoptosis. Finally, miRNA-gene network analyses identified miRNA-125b as a crucial miRNA in GC development. Taken together, these results develop a comprehensive expression and functional profile of differentially expressed miRNAs related to gastric oncogenesis. This profile may serve as a potential tool for biomarker and therapeutic target identification in GC patients.